Using height-adjusted stunting prevalence will fail disadvantaged children worldwide - Leroy, Jef L.; Frongillo, Edward A.; Borghi, Elaine (Elsevier, 2022)
In their Comment (February, 2022), S V Subramanian and colleagues challenge the validity of using the prevalence of child stunting to monitor and evaluate nutrition policies. Their argument is based on a fundamental misunderstanding of the 2006 WHO growth standards and how to appropriately use and interpret stunting. The authors espouse a dangerous and unethical position.